Optimization and Comparison of Biodiesel Production Process by Electric Heating and Microwave-Assisted Heating Transesterification for Waste Cooking Oil via One-Way Experiments and ANOVA - Li, Wenjing; Li, Guangming; Wang, Fan; Zhu, Haochen; He, Wenzhi; Huang, Juwen (Frontiers in Environmental Science, 2022)
Base-catalyzed transesterification of waste cooking oils (WCOs) into biodiesel is a widely used renewable fuel production technology. The traditional heating method for this process is electric heating (EH), and microwave-assisted heating (MW) has also received extensive attention in recent years. This study compared the two reaction processes in detail by one-way experiments and ANOVA. Catalyst content, reaction temperature (average temperature) and alcohol-oil molar ratio are key factors for these two transesterification processes. The maximum FAME yield of EH and MW process both appeared at 1.0% catalyst concentration, the reaction temperature around 60 °C, while the MW process called for more methanol. It was speculated that the acid value of WCOs may be closely related to the time required for transesterification as well. The MW process can improve transesterification efficiency, which is shown in kinetics as much larger than the reaction constant of the EH process and about one tenth of the activation energy.